PEMBELAJARAN PROBLEM BASE LEARNING BERBASIS ANIMASI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Mukhlis Mukhlis; Arusman Arusman (UIN AR-RANIRY, 2020)
This animation-based PBL model research was conducted at MAN 4 Pidie Jaya, the research subjects were 34 class XI students. The research objective was to determine the increase in CBC and student response. This type of research is a quasi-experimental design with a pretest and posttest one group design, involving 1 (one) study group that is given an animation-based PBL learning model. Processing of research results using the T-test and N-Gain test. The results showed the mean scores for the initial and final CBC tests were 48.50 and 73.25. The t-test value of the statistical test t = 7.02 and tt = 1.70, so that t> tt, learning animation-based PBL models on Basic Law and Chemical Computing has an effect on students' CBC skills. The average value of the Gain and N-Gain test for the CBC ability of students was 24.75 and 0.48 or 48% were in the